2022
DOI: 10.1002/jgc4.1592
|View full text |Cite
|
Sign up to set email alerts
|

Use of a chatbot to increase uptake of cascade genetic testing

Abstract: Successful proband‐mediated family communication and subsequent cascade genetic testing uptake requires interventions that present information clearly, in sufficient detail, and with medical authority. To facilitate family communication for patients receiving clinically actionable results via the MyCode® Community Health Initiative, a Family Sharing Tool (FST) and a cascade chatbot were developed. FST is an electronic mechanism allowing patients to share genetic test results with relatives via chatbot. The cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Much of the previous research has focused on tool mechanics and clinical impacts (Ireland et al 2021 ; Nazareth et al 2021 ; Sato et al 2021 ), whereas our work examined patient preferences through qualitative interviews. Work that has been conducted on patient acceptability of chatbots within genetics has been limited to a narrow set of functions or has been assessed within the adult cancer and screening populations (Nazareth et al 2021 ; Schmidlen et al 2019 , 2022 ; Siglen et al 2021 ; Wang et al 2015 ), whereas our work has examined acceptability within a range of diagnostic genetic testing scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Much of the previous research has focused on tool mechanics and clinical impacts (Ireland et al 2021 ; Nazareth et al 2021 ; Sato et al 2021 ), whereas our work examined patient preferences through qualitative interviews. Work that has been conducted on patient acceptability of chatbots within genetics has been limited to a narrow set of functions or has been assessed within the adult cancer and screening populations (Nazareth et al 2021 ; Schmidlen et al 2019 , 2022 ; Siglen et al 2021 ; Wang et al 2015 ), whereas our work has examined acceptability within a range of diagnostic genetic testing scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…In genomics, chatbots are being developed to assist with delivering various components of care (Heald et al 2020 ; Ireland et al 2021 ; Nazareth et al 2021 ; Sato et al 2021 ; Schmidlen et al 2019 ; Siglen et al 2021 ). For example, chatbots exist or are in development to support patients with pre-test counseling, result disclosure, communication with the health care team, notification of family members about results or the availability of cascade testing, and attending to distress and anxiety (Heald et al 2020 ; Ireland et al 2021 ; Nazareth et al 2021 ; Sato et al 2021 ; Schmidlen et al 2022 , 2019 ). However, much of the research into chatbots has focused on their medical accuracy (Nazareth et al 2021 ; Sato et al 2021 ), feasibility (Heald et al 2020 ), or potential impact on knowledge and decision-making (Ireland et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When considering approaches to encouraging at-risk relatives to ultimately seek cascade testing, programs have been designed to offer cascade testing at reduced rates or at no-charge for relatives ( Aktan-Collan et al, 2007 ; Caswell-Jin et al, 2019 ; Courtney et al, 2019 ; Invitae, 2021 ). Preliminary findings in a recent study demonstrated that chatbots are an effective means to facilitating cascade testing (data in press Schmidlen et al, 2022 ). Regardless of the approach, it is critical that methods used to encourage both results sharing and subsequent cascade testing are accessible to diverse populations ( Milo Rasouly et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%